2016
DOI: 10.1007/s10029-016-1534-2
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal wall integrity after open abdomen: long-term results of vacuum-assisted wound closure and mesh-mediated fascial traction (VAWCM)

Abstract: Vacuum-assisted wound closure and mesh-mediated fascial traction (VAWCM) seem to result in low complication rates and high fascial closure rates. Abdominal wall reconstruction, which is a challenging and complex procedure and causes considerable patient discomfort, can thus be avoided in the majority of cases. Available results are based on studies involving only a small number of cases. Multi-centre studies and registry-based data are therefore needed to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…NPWT is a highly effective method of wound closure with much better results than temporary closure [ 7 , 12 ]. Furthermore, treatment outcomes (wound closure) have been shown to improve dramatically by adding mesh traction [ 6 , 8 , 13 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…NPWT is a highly effective method of wound closure with much better results than temporary closure [ 7 , 12 ]. Furthermore, treatment outcomes (wound closure) have been shown to improve dramatically by adding mesh traction [ 6 , 8 , 13 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incisional hernia rate ranged from 21% at 21 months follow up to 54% at 63 months of follow up. The incisional hernia repair rate was 42% [15] and 33% [14] in the two large prospective studies, respectively. The study patients reported lower short form health survey (SF-36) scores than the mean reference population, mainly dependent on the prevalence of major co-morbidity [14].…”
Section: Study Characteristics Of Long-term Outcome Studiesmentioning
confidence: 92%
“…In 2007, the first report of a modified technique combining vacuum-assisted wound closure with mesh-mediated fascial traction (VAWCM) for long-term therapy of the open abdomen was published [5]. Since then, several centres have adopted this technique and reported their experiences [6][7][8][9][10][11][12][13][14][15]. The aim of this systematic review was to report the short-term and long-term results for the VAWCM technique.…”
mentioning
confidence: 99%
“…Bauchwandhernien sind die häufigste Langzeitkomplikation nach OAT: Als "geplante Hernie" sind sie natürliche Folge der Unmöglichkeit des Faszienverschlusses nach der abdominalen Katastrophe und als "Narbenhernie nach sekundärem Faszienverschluss" eine Folge der Strukturschwächung der Bauchwand. Die Hernieninzidenz nach OAT liegt neueren Arbeiten zufolge bei 35-66 % nach 4 Jahren [22]. Narbenhernien sind mit einer Reduktion der Funktionalität der Bauchdecke, Schmerzen, Inkarzerationsrisiko und der Notwendigkeit von ggf.…”
Section: Secondunclassified